1912
DOI: 10.1084/jem.15.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Lesions of Subacute Bacterial Endocarditis

Abstract: 1. In most cases of chronic or subacute bacterial endocarditis due to the endocarditis coccus (Streptococcus viridans), there exists a distinctive pathological lesion in some of the glomeruli due to bacterial emboli. 2. The salient features of the pathological picture are first, the involvement of one or more loops of a variable number of glomeruli; secondly, the absence of any visible disease in the uninvolved glomeruli and in the uninvolved portions of affected glomeruli; and thirdly, the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1923
1923
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…15 He used the term “fungus” to describe “wart-like excrescences” occurring in an 18-year-old patient who also had abscess formation at the aortic root. This report was also the first to document peripheral embolization, later described in greater detail almost a century later by Löhlein and Baehr 16 , 17…”
mentioning
confidence: 53%
“…15 He used the term “fungus” to describe “wart-like excrescences” occurring in an 18-year-old patient who also had abscess formation at the aortic root. This report was also the first to document peripheral embolization, later described in greater detail almost a century later by Löhlein and Baehr 16 , 17…”
mentioning
confidence: 53%
“…'Focal embolic nonsuppurative glomerulonephritis' [2] is the most typical renal lesion complicating bacterial endocarditis. It corresponds to a focal and segmental pro liferative glomerular lesion [5], Earlier investigators [2,11] thought nephritis resulted primarily from emboli aris ing from infected valves.…”
Section: Discussionmentioning
confidence: 99%
“…It corresponds to a focal and segmental pro liferative glomerular lesion [5], Earlier investigators [2,11] thought nephritis resulted primarily from emboli aris ing from infected valves. However, another paper [4] reported that there was no evidence to implicate emboli of bacterial vegetations in the pathogenesis [4], Other types of nephritis have been described: diffuse proliferative GN predominates in bacterial endocarditis whatever the cau sative organ ism [12] whether with or without extracapilla ry proliferation [5],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led him to suggest that septic emboli account for the glomerular lesions which he termed 'embolic nonsup purative focal nephritis'. Two years later, Baehr [14] reported the same lesions in 21 of 25 cases of bacterial endocarditis, in 5 of which he noted bacterial emboli and in 2 a diffuse glomerulonephritis. In a subsequent report [ 15] of 9 patients with bacterial endocarditis who died of uremia, diffuse glomerulonephritis was noted to be present in all 9 cases and characterized as acute in 2 and chronic in 7 of them.…”
Section: Dr Eknoyanmentioning
confidence: 99%